Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acschemneuro.0c00714
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Structure of Toxic Amyloid-β Oligomers with Electron Spin Resonance and Molecular Modeling

Abstract: Structural models of the toxic species involved in the development of Alzheimer's disease are of utmost importance to understand the molecular mechanism and to describe early biomarkers of the disease. Among toxic species, soluble oligomers of amyloid-β (Aβ) peptides are particularly important, because they are responsible for spreading cell damages over brain regions, thus rapidly impairing brain functions. In this work we obtain structural information on a carefully prepared Aβ(1-42) sample, representing a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 99 publications
1
13
0
Order By: Relevance
“…This phenomenon is affected by specific lipids including cholesterol, sphingomyelin, and gangliosides [717,718]: lipid types typically present in the outer leaflet of the cell membrane. Amyloid fibers at a membrane surface have thus been frequently studied using MD simulations, e.g., [719][720][721][722][723][724][725][726][727][728][729][730], however, a surprisingly small fraction of this work has been performed in the context of drug design [731,732]. Khondker et al, proposed designing drugs with a mode of action that involved modulating membrane properties to affect the aggregation of amyloid-β25-35 at the bilayer surface [229].…”
Section: Can Drugs Prevent Amyloid Formation Via the Modification Of Membrane Properties?mentioning
confidence: 99%
“…This phenomenon is affected by specific lipids including cholesterol, sphingomyelin, and gangliosides [717,718]: lipid types typically present in the outer leaflet of the cell membrane. Amyloid fibers at a membrane surface have thus been frequently studied using MD simulations, e.g., [719][720][721][722][723][724][725][726][727][728][729][730], however, a surprisingly small fraction of this work has been performed in the context of drug design [731,732]. Khondker et al, proposed designing drugs with a mode of action that involved modulating membrane properties to affect the aggregation of amyloid-β25-35 at the bilayer surface [229].…”
Section: Can Drugs Prevent Amyloid Formation Via the Modification Of Membrane Properties?mentioning
confidence: 99%
“… 29 Recent experiments have also shown that cell toxicity is associated with nanoparticles of about 4 nm in height. 30 Such nanoparticles fit with annular assemblies of three tetramers or dodecamers. For comparison with the dodecamer, we used a model of mature fibrils which have 12 Aβ42 chains.…”
Section: Introductionmentioning
confidence: 99%
“…In both, the S1 and S2 segments comprise a parallel β‐sheet with a bend near the center of S1. Banchelli et al 42 found that Cu ++ causes formation of dimers by binding between His6 and His13 or His14 of two Aβ monomers. They concluded that at least portions of adjacent S1 segments are antiparallel (consistent with some of our models) rather than in‐register parallel.…”
Section: Introductionmentioning
confidence: 99%